Management of Renal Vascular Injuries by Angioembolization in a Low Resource Setting: A Case Series with Review of Literature - Saifullah Khalid ,; Manzoor Ahmad,; Ezaz Ahmed,; Wasif Mohammad Ali,; Ali, Imad (Acta medica Lituanica, 2024)
Background: Renal vascular injuries, like renal artery pseudoaneurysms and arteriovenous fistulas, are rare but serious complications following renal procedures and trauma. Standard management requires costly microcatheters for angioembolization. This study investigates a cost-effective method using diagnostic catheters and affordable coils in a low-resource setting.Methods: We analyzed five patients from December 2023 to June 2024 who had persistent hematuria or hemoglobin drops after renal intervention or trauma. CT angiography identified their injuries, and angioembolization was performed with diagnostic catheters and coils, reducing procedural costs.Results: The use of diagnostic catheters and coils successfully managed all cases. Patients experienced resolution of hematuria and were discharged in 2–3 days. Follow-up over three months revealed no recurrence or significant renal function issues.Conclusion: Diagnostic catheters and coils offer an effective method for managing renal vascular injuries in resource-limited settings, achieving satisfactory outcomes with minimal morbidity.
Keywords: Renal vascular injury; Angioembolization; Diagnostic catheter; Low resource setting